2016
DOI: 10.1193/051214eqs067m
|View full text |Cite
|
Sign up to set email alerts
|

Using Remote Sensing for Building Damage Assessment: GEOCAN Study and Validation for 2011 Christchurch Earthquake

Abstract: This study explores the performance of GEOCAN, a remote-sensing and crowdsourcing platform for assessing earthquake damage, by using geo-referenced ground-based damage assessments. This paper discusses methods for the application of remote sensing in post-earthquake damage assessment and reports on a GEOCAN crowd-sourcing study following the 22 February 2011 Christchurch event and its validation using field studies. It describes the principal data sets used, discusses in detail the problems of validation, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…Estimating damage from remote sensing data, such as satellite photography, has been widely performed recently (Booth et al 2011; Foulser-Piggott et al 2016). Comparing the damage levels found in the field survey and photo analysis showed that photo analysis is a reasonable method to identify story-collapsed buildings (D5), but it is difficult to identify D4 buildings (tilted buildings without story collapse).…”
Section: Discussionmentioning
confidence: 99%
“…Estimating damage from remote sensing data, such as satellite photography, has been widely performed recently (Booth et al 2011; Foulser-Piggott et al 2016). Comparing the damage levels found in the field survey and photo analysis showed that photo analysis is a reasonable method to identify story-collapsed buildings (D5), but it is difficult to identify D4 buildings (tilted buildings without story collapse).…”
Section: Discussionmentioning
confidence: 99%
“…The use of imaging technology has been increasing rapidly as data gathering, and enriching tool boosting mission capabilities and ensure their safe deployment in areas affected by earthquakes [35]. For about the last decade, high-resolution optical satellite and aerial images have been increasingly used for a rapid building-damage survey after an earthquake [25]; they have become an important tool for rapid and reliable structural damage assessment (SDA) [22]. We identified in our literature review six RS data sources used for earthquake reconnaissance.…”
Section: Remote Sensing (Rs)mentioning
confidence: 99%
“…The result of the damage assessment will be the aggregate quantities of damages for an exposure unit. This quantitative assessment is used to assess the direct economic loss as the basis for calculating the value of economic losses: the replacement cost [19] or insurance payouts of value to international aid organisation, bi-lateral/multilateral donors and the insurance industry [25]. During the emergency or relief phase, the quantitative assessment of damage starts with the structural component of the buildings due to its essential role in the safety of the population affected by earthquakes and the estimation of temporary shelter needed [9].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, identifying noncollapsed damage states is a more challenging task. For instance, Foulser-Piggott et al (2016) attempted to identify the red-tagged or yellow-tagged noncollapsed buildings from the 2011 Christchurch earthquake, and the omission error was found to be 56%-86%. Note that currently there is no feasible solution to effectively reduce such an error.…”
Section: Identification Of Collapsed Buildingsmentioning
confidence: 99%